Radiofrequency identification and medical devices: the regulatory framework on electromagnetic compatibility. Part I: medical devices. (May 2012) - Censi, Federica; Mattei, Eugenio; Triventi, Michele; Bartolini, Pietro; Calcagnini, Giovanni
Radiofrequency identification (RFID) technology has acheived significant success and has penetrated into various areas of healthcare. Several RFID-based applications are used in various modalities with the ultimate aim of improving patient care. When a wireless technology is used in a healthcare environment, attention must be paid to the potential risks deriving from its use; one of the most important being electromagnetic interference with medical devices. In this paper, the regulatory framework concerning the electromagnetic compatibility between RFID and medical devices is analyzed to understand whether and how the application of the current standards allows for the effective control of the risks of electromagnetic interference.